Our Experience with Mediastinoscopy and Mediastinotomy (Chamberlain) - Carusso, Enrique; Vassallo, Bartolomé (Cirugía del Uruguay, 1980)
From 1/1/75 to 10/31/79 it was done 166 Mediastinoscopies and 32 anterior Mediastinotomies ( Chamberlain), at the Thoracic Section, Surgery Service of Italian Hospital of Buenos Aires.